2019
DOI: 10.1021/acs.oprd.9b00233
|View full text |Cite
|
Sign up to set email alerts
|

Data-Rich Experimentation Enables Palladium-Catalyzed Couplings of Piperidines and Five-Membered (Hetero)aromatic Electrophiles

Abstract: To circumvent a current limitation in palladium-catalyzed C–N cross-coupling methodology, high-throughput experimentation was used to identify a catalyst capable of fusing piperidine-based nucleophiles with five-membered (hetero)­aromatic bromides. A decomposition pathway for the standard electrophile was found, and a base screen was used to identify conditions that suppress this undesired transformation. Building on this, systematic optimization using a Design of Experiments approach delivered mild reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…Upon analysis of the predictive model's most significant descriptors, the authors proposed that the principle cause of poor performance of isoxazoles in Pd‐catalyzed coupling reactions is competing oxidative addition of the weak N−O bond. This proposal was validated through subsequent mechanistic experiments and together, these results provide important guidance for further development of cross‐coupling reactions of 5‐membered heteroarenes [97] …”
Section: Organic Superbases In High‐throughput Experimentationmentioning
confidence: 70%
“…Upon analysis of the predictive model's most significant descriptors, the authors proposed that the principle cause of poor performance of isoxazoles in Pd‐catalyzed coupling reactions is competing oxidative addition of the weak N−O bond. This proposal was validated through subsequent mechanistic experiments and together, these results provide important guidance for further development of cross‐coupling reactions of 5‐membered heteroarenes [97] …”
Section: Organic Superbases In High‐throughput Experimentationmentioning
confidence: 70%
“…9,11 However, identifying suitable reaction conditions and then optimizing a given C-N coupling reaction can remain time-consuming. Despite the broad adoption of high-throughput experimentation 12 in recent years, the large number of possibilities precludes exhaustive screening of reaction space. Self-guiding experiments 13 can help, but the value of such experiments can be limited when the response curves are steep, as they are oen for catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ahnemann et al 14 created a yield-predicting model for the coupling of aryl halides with 4-methylaniline in the presence of different additives, where the data came from high-throughput experimentation. Sather and Martinot 12 found through high-throughput experimentation working reaction conditions for piperidine-based nucleophiles with five-membered hetero-aromatic bromides, a known difficult class of BH substrates. Similar cases exist for other reactions such as deoxyfluorinations 15 or thiol additions 16 and more recently, Sandfort et al have reported an approach based on fingerprints performing well at various chemical prediction tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The Buchwald-Hartwig amination (Scheme 3a) has been one of the least understood transformations despite wide efforts to improve our mechanistic insights. Sather and Martinot [39] investigated CÀ N coupling with challenging five membered heteroaromatic electrophiles and piperidine-based nucleophiles that often lead to side reactions like β-hydride elimination and protodehalogenation. Their work employed an initial HTE focused on catalyst identification followed by a scan of catalyst loadings.…”
Section: Buchwald-hartwig Aminationmentioning
confidence: 99%